Humor as a Political Act: Study of Indonesian Presidents’ Humor - Surahmat Surahmat; I Dewa Putu Wijana; Suryo Baskoro (Universitas Sanata Dharma, 2023)
This study aims to explain the use of humor by Indonesian presidents for political communication. Presidents’ use of humor is an interesting phenomenon, given that they are social subjects who wield great power within a country. Their social position leads to different characteristics and social impacts due to the humor used. This research uses a qualitative descriptive approach. Data was collected from books, news sites, and YouTube channels documenting the humor of the three Indonesian presidents. Data were then analyzed using pragmatic analysis. The results show that presidential humor varies according to personal preferences, speech objectives, and contexts. Presidents use joke, conversational humor, and pun to joke, tease, praise, satirize, criticize, and delegate power. Joking, teasing, and praising are used on friends and political allies. Meanwhile, satirizing and criticizing are applied to political opponents. Humor is a middle ground for presidents, enabling them to achieve speech objectives without explicitly expressing their intention. Politically, humor functions to (1) represent oneself positively and represent opponents negatively, (2) build relationships and positioning with opponents and allies, and (3) exercise control and discipline. However, the relationship between form, style, and illocutionary of presidential humor is often ambiguous. Such conditions seem related to political relations' dynamic and equal nature, where friends and foes are not always crystal clear.